Morphosyntactic Analysis of Mro Language - Rashel, Md Mostafa (Dhaka University Journal of Linguistics, 2010)
In this article, I have used many examples to build up a concept about the relationship between Mro morphology and syntax, especially the different case markers to find out the relationship among them. During the research my goal was to provide a description of the constituent order; grammatical categories like tense; comparative marker -la'e (then), -leplep la'e (most); pronominal system (determiners used with first and second person but 3rd person is independent); demonstratives, adverbs, clause combination like conditional markers, reasons, time, motion; structures of question like y/n question, informal, exclamatory; case markers like noun, pronoun (relative), numeral relation to conjunction, suffix, clause/sentence level; grammatical relation (GR) as well as text analysis of Mro language. Key words: Morphosyntax, Language family, pronominal system, Case marker, grammatical relation, Mro. DOI: 10.3329/dujl.v2i3.4149 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 141-160